Aquatic macroinvertebrates survey and assessment of two artificial reservoirs into conservation units from the Southeast Region of Brazil - Silva, Fabio Laurindo da; Pauleto, Gustavo Mayer; Ruiz, Sonia Silveira; Talamoni, Jandira Liria Biscalquini [UNESP] (My University, 2011)
This study aims to inventory and assess the aquatic macroinvertebrates fauna in two artificial reservoirs into conservation units with differences regarding conservation level and to anthropogenic impacts. The samplings were carried out in Caetetus Ecological Station and Bauru City Zoological Park, where some physical and chemical variables also were measured. The results obtained indicated that the Caetetus Ecological Station is more effective in the conservation of the diversity of aquatic macroinvertebrates compared to Bauru City Zoological Park. These results can be attributed to the strong anthropogenic impact suffered by the reservoir in Bauru and demonstrate the importance of these areas in maintaining the diversity of aquatic macroinvertebrates community.

Este estudo objetivou inventariar e avaliar a fauna de macroinvertebrados aquáticos em dois reservatórios artificiais localizados em unidades de conservação com diferentes níveis de conservação e impactos antrópicos. As amostragens foram realizadas na Estação Ecológica de Caetetus e no Zoológico Municipal de Bauru, onde algumas variáveis físicas e químicas também foram aferidas. Os resultados obtidos indicam que a Estação Ecológica de Caetetus é mais efetiva na conservação da diversidade de macroinvertebrados aquáticos comparada ao Zoológico Municipal de Bauru. Estes resultados podem ser atribuídos ao forte impacto antropogênico sofrido pelo reservatório em Bauru e demonstra a importância destas áreas na manutenção da diversidade da comunidade de macroinvertebrados aquáticos.
Levantamento e avaliação dos macroinvertebrados aquáticos em dois reservatórios artificiais em unidades de conservação da região sudeste do Brasil
Keywords: Chironomidae; Conservation units; Diversity; Ecology; Reservoir; Unidades de conservação; Chironomidae; Diversidade; Reservatório; Ecologia